Novel substrate-based inhibitors of human glutamate carboxypeptidase II with enhanced lipophilicity - Plechanovová, Anna; Byun, Youngjoo; Alquicer, Glenda; Skultétyová, L'ubica; Mlčochová, Petra; Němcová, Adriana; Kim, Hyung-Joon; Navrátil, Michal; Mease, Ronnie; Lubkowski, Jacek; Pomper, Martin; Konvalinka, Jan; et al. (Journal of medicinal chemistry, 2011)
Virtually all low molecular weight inhibitors of human glutamate carboxypeptidase II (GCPII) are highly polar compounds that have limited use in settings where more lipophilic molecules are desired. Here we report the identification and characterization of GCPII inhibitors with enhanced liphophilicity that are derived from a series of newly identified dipeptidic GCPII substrates featuring nonpolar aliphatic side chains at the C-terminus. To analyze the interactions governing the substrate recognition by GCPII, we determined crystal structures of the inactive GCPII(E424A) mutant in complex with selected dipeptides and complemented the structural data with quantum mechanics/molecular mechanics calculations. Results reveal the importance of nonpolar interactions governing GCPII affinity toward novel substrates as well as formerly unnoticed plasticity of the S1' specificity pocket. On the basis of those data, we designed, synthesized, and evaluated a series of novel GCPII inhibitors with enhanced lipophilicity, with the best candidates having low nanomolar inhibition constants and clogD > -0.3. Our findings offer new insights into the design of more lipophilic inhibitors targeting GCPII.
Keywords: Substrate Specificity; Dipeptides; Thermodynamics; lidé; kvantová teorie; vztahy mezi strukturou a aktivitou; Antigens, Surface; Mutagenesis, Site-Directed; Kinetics; glutamátkarboxypeptidasa II; Humans; Binding Sites; kinetika; Structure-Activity Relationship; substrátová specifita; konformace proteinů; krystalografie rentgenová; Protein Conformation; Quantum Theory; dipeptidy; Crystallography, X-Ray; molekulární modely; ligandy; antigeny povrchové; Ligands; Glutamate Carboxypeptidase II; mutageneze cílená; vazebná místa; Models, Molecular; termodynamika